Increasing broadband radiation of sub‐6 GHz base station antenna based on sector dipole mode optimization. Issue 12 (13th November 2022) - Rao, Sheng‐Lin; Cai, Qiang‐Ming; Zhang, Runren; Chen, Tang; Liu, Mulin; Liu, Tao; Cao, Xin; Zhu, Yuying; Zhu, Yuyu; Pu, Bo; Fan, Jun
Abstract: A broadband radiation dual‐polarized antenna is proposed for the application of 5G sub‐6 GHz base stations. The radiator of the antenna is consisted of a pair of crisscrossed sector dipoles, and is fed by microstrip stubs. By etching rectangular slots on the patches, the resonant modes of the antenna can increase to eight. Therefore, the broadband characteristic can be realized by effectively exciting the ideal modes. And the dual‐polarized characteristic is also achieved by exciting the ideal modes. The overall size of the proposed antenna is λ × λ × 0.258 λ ( λ is the free‐space wavelength at 4.3 GHz) and it is fabricated and tested. The measured bandwidth can achieve 47.2% (3.19 ~ 5.22 GHz) for S 11 <−10 dB and S21 < −26 dB, and the half‐power beam width (HPBW) is 55 ± 6° within the working band. The antenna gain attains 8.3 ± 1.6 dBi with a good stable radiation pattern. These features make the antenna more attractive for 5G sub‐6 GHz communication applications.